The Effect of Work Discipline, Work Motivation, and Compensation on Employee Productivity: A Case Study at Z Hospital - Abdul Rahmat; R. Jokosugiharjo; Alyssa Edwina Imad Khalid Bakhour (Jurnal Bisnis dan Manajemen, 2025)
This study aims to examine the effect of work discipline, work motivation, and compensation on employee productivity at Z Hospital. The study employs a quantitative approach using both primary and secondary data. The population consists of permanent employees of Z Hospital, with a sample of 178 respondents selected through probability sampling. Data were collected through questionnaires, observation, and literature review. The data analysis techniques include descriptive analysis, instrument testing, classical assumption testing, hypothesis testing, and multiple linear regression analysis using SPSS version 27. The regression results indicate that work discipline does not have a significant effect on employee productivity, work motivation has a negative and significant effect on employee productivity, while compensation has a positive and significant effect on employee productivity. These findings suggest that compensation plays a dominant role in influencing productivity, whereas motivation and discipline function more as baseline behavioral factors within the organizational context of the hospital.